Analisis Kepatuhan Penggunaan Alat Pelindung Diri (APD) Pada Peserta Pelatihan Keterampilan Tukang dan Pekerja Konstruksi - Mafra, Ramadisu; Riduan, Riduan; Zulfikri, Zulfikri (Universitas muhammadiyah palembang, 2021)
Compliance of personal protective equipment (PPE) uses without the impact of the consequences is a reflection of a good workforce. This compliance is thought to be influenced by various factors, such as knowledge, attitudes, years of service, comfort, suitability of PPE and type of work and availability. The phenomenon of non-compliance cannot be ignored, and is evident from several previous studies. This study aims to measure the level of compliance, reasons and factors that influence it. Involving 80 participants who participated in builder skills training. Collecting data using K3 logbook, surveillance camera recordings and field observations, the data were processed by cross sectional analysis to see causality and choreation. The results showed that the level of compliance using PPE correctly was 82.92% on average. The average level of compliance with individual behavior is 66.25%. Non-compliance with the use of PPE safety helmet 29.00%, cotton glove 19.38%, safety vest 16.25% and safety boot 3.44%, with reasons of forgetting 33.85%, PPE is considered to be disturbing 26.67%, feeling uncomfortable 26.15% and the attitude of feeling that they will not be harmed by 13.33%, which is influenced by the factors of unsafe work habits without PPE, years of service, the harmony of PPE types and work, and there is no relationship between knowledge and compliance with the use of PPE. Repetitive non-compliance did by 30,00% participants.